Readers´ study - General public - Weibull, Lennart; Aldemark, Lars (University of Gothenburg, 1982)
The study is part of the research program The Role of the Press in Society, a project initiated by the 1972 Commission of the Press and with a general aim to analyze the significance of mass media in Sweden. The aim of ´Readers´ study - the general public´ was to study the consumption of various types of media; daily press, popular and specialist press, and radio and television. To make it possible to adapt the consumption habits in a wider perspective questions were also put about among other things political interests and engagement, freetime activities and knowledge about various society issues. To make parallel analyses possible with other studies within the research project questions were also put regarding what was thought to dominate local society debate and about events which were actual at the time. A supplementary study to the above mentioned receiver study was carried out at April 26th 1974. The local newspaper generally read by the respondent was distributed to these together with a questionnaire. The respondents were asked to mark the articles read. Questions were also asked about the radio and television consumption the night before. These data can be compared with the total content of the newspaper, see SSD 0131.

The study is part of the research program The Role of the Press in Society, a project initiated by the 1972 Commission of the Press and with a general aim to analyze the significance of mass media in Sweden. The aim of ´Readers´ study - the general public´ was to study the consumption of various types of media; daily press, popular and specialist press, and radio and television. To make it possible to adapt the consumption habits in a wider perspective questions were also put about among other things political interests and engagement, freetime activities and knowledge about various society issues. To make parallel analyses possible with other studies within the research project questions were also put regarding what was thought to dominate local society debate and about events which were actual at the time. A supplementary study to the above mentioned receiver study was carried out at April 26th 1974. The local newspaper generally read by the respondent was distributed to these together with a questionnaire. The respondents were asked to mark the articles read. Questions were also asked about the radio and television consumption the night before. These data can be compared with the total content of the newspaper, see SSD 0131.
Pressens funktioner: Läsarstudien - Allmänheten
Keywords: Media; Media; Social Sciences; Samhällsvetenskap